Challenges in migrating legacy software systems to the cloud — an empirical study. (July 2017) - Gholami, Mahdi Fahmideh; Daneshgar, Farhad; Beydoun, Ghassan; Rabhi, Fethi
Highlights: Deriving a set of important process elements to be incorporated into legacy system migration to cloud platforms. Facilitates understanding the underlying structure of the cloud migration process by unifying and distilling cumulated knowledge in the literature along with domain experts' advice. Providing a tool for organisations to analyse and appraise their acquisition method alternatives (e.g. in-house or off-the-shelf methods) for their extent of support of cloud migration. Abstract: Moving existing legacy systems to cloud platforms is a difficult and high cost process that may involve technical and non-technical resources and challenges. There is evidence that the lack of understanding and preparedness of cloud computing migration underpin many migration failures in achieving organisations' goals. The main goal of this article is to identify the most important challenging activities for moving legacy systems to cloud platforms from a perspective of reengineering process. Through a combination of a bottom-up and a top-down analysis, a set of common activities is derived from the extant cloud computing literature. These are expressed as a model and are validated using a population of 104 shortlisted and randomly selected domain experts from different industry sectors. We used a Web-based survey questionnaire to collect data and analysed them using SPSS Sample T-Test. The results of this study highlight the most important and critical challenges that should be addressed by various roles within a legacy to cloud migration endeavour. The study provides an overall understanding of this process including common occurring activities, concerns and recommendations. In addition, the findings of this study constitute a practical guide to conduct this transition. This guide is platform agnostic and independent from any specific migration scenario, cloud platform, or an application domain.